La triple démarche de l'enseignant en contexte hypermoderne - André Pachod (Nantes Université, 2017)
Situated in a hypermodern context characterized by new relationships in time, in others, oneself, the knomledge, the teacher is invited to activate a triple approach. The first, of sociological nature, the fact of evolving in a contemporary environment to know and understand in its evolutions, its realities, its waitings, its contradictions, its challenges. The second approach, of a philosophical and anthropological nature, locates the teacher in front of or in the face of this hypermodernity, inviting it to stop to question the educational offer and to follow certain orientations. The third approach is resolutely ethical: whithin its class and school, it acts in an ethical way by deciding priorities with the service of the success of the pupil.